2017
DOI: 10.1111/twec.12570
|View full text |Cite
|
Sign up to set email alerts
|

China's exports, export tax rebates and exchange rate policy

Abstract: This paper examines the relationship between China's exports, export tax rebates and exchange rate policy. It offers an explanation for why China's exports continued to rise under RMB real appreciations during the Asian financial crisis. Based on a traditional export demand model, we test our hypothesis that the counteracting effects of China's export tax rebate policy have diminished the effectiveness of real exchange rates in facilitating the resolution of trade imbalances under the current pegged exchange r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Many previous studies suggest that export tax rebate policy, which are important policy tools for governments, are often used to stimulate export (Chong'En et al, 2011;Lee et al, 2021) and firm productivity (Zhang, 2019), thereby promoting economic growth (Xu, 2018). Few studies have explored the impact of the export tax rebate policy adjustment that may lead to environmental improvements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies suggest that export tax rebate policy, which are important policy tools for governments, are often used to stimulate export (Chong'En et al, 2011;Lee et al, 2021) and firm productivity (Zhang, 2019), thereby promoting economic growth (Xu, 2018). Few studies have explored the impact of the export tax rebate policy adjustment that may lead to environmental improvements.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, in order to adjust the product structure of foreign trade and encourage the increase of the proportion of trade exports of environment-friendly enterprises, China reduced the export tax rebate rates of some highly polluting, energy-consuming and resource-based products. At the same time, the export tax rebate rates for IT products and pharmaceutical products were raised to stimulate the trade competitiveness of low energy-consuming and innovative enterprises (Xu, 2018;Braakmann et al, 2020). In 2007, the Chinese central government adjusted the export tax rebate policy again.…”
mentioning
confidence: 99%
“…An et al (2017) explored regional effect of export tax rebate on exporting enterprise in China. Z. H. Xu (2018) found that the counteracting effects of China's export tax rebate policy affected the effectiveness of real exchange rates in facilitating the resolution of trade imbalances under background of the pegged exchange rate regime. D. Y.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, China needs to maintain or depreciate the exchange rate because a rise in "Yuan" is expected to drop the export revenue because of very low elasticity. China's exchange rate policy is such a highly argumentative and extensively discussed issue that it often generates heated debate around the globe [70][71][72]. The United States of America has criticized China's exchange rate policy for the two country's bilateral trade deficit [73][74][75].…”
Section: Plos Onementioning
confidence: 99%